Decline in low-density lipoprotein cholesterol concentration: lipid-lowering drugs, diet, or physical activity? Evidence from the Whitehall II study. Issue 11 (12th April 2011) - Bouillon, Kim; Singh-Manoux, Archana; Jokela, Markus; Shipley, Martin J; Batty, G David; Brunner, Eric J; Sabia, Séverine; Tabák, Adam G; Akbaraly, Tasnime; Ferrie, Jane E; Kivimäki, Mika
Abstract : Objective: To examine the association of lipid-lowering drugs, change in diet and physical activity with a decline in low-density lipoprotein (LDL) cholesterol in middle age. Design: A prospective cohort study. Setting: The Whitehall II study. Participants: 4469 British civil servants (72% men) aged 39–62 years at baseline. Main Outcome Measure: Change in LDL-cholesterol concentrations between the baseline (1991–3) and follow-up (2003–4). Results: Mean LDL-cholesterol decreased from 4.38 to 3.52 mmol/l over a mean follow-up of 11.3 years. In a mutually adjusted model, a decline in LDL-cholesterol was greater among those who were taking lipid-lowering treatment at baseline (−1.14 mmol/l, n=34), or started treatment during the follow-up (−1.77 mmol/l, n=481) compared with untreated individuals (n=3954; p<0.001); among those who improved their diet—especially the ratio of white to red meat consumption and the ratio of polyunsaturated to saturated fatty acids intake—(−0.07 mmol/l, n=717) compared with those with no change in diet (n=3071; p=0.03) and among those who increased physical activity (−0.10 mmol/l, n=601) compared with those with no change in physical activity (n=3312; p=0.005). Based on these estimates, successful implementation of lipid-lowering drug treatment for high-risk participants (n=858) and favourable changes in diet (n=3457) and physical activity (n=2190) among those with non-optimal lifestyles would reduce LDL-cholesterol by 0.90 to 1.07 mmol/l in the total cohort. Conclusions: Both lipid-lowering pharmacotherapy and favourable changes in lifestyle independently reduced LDL-cholesterol levels in a cohort of middle-aged men and women, supporting the use of multifaceted intervention strategies for prevention.